UWB Metamaterial-Loaded Antenna for C-Band Applications - Parul Dawar; N. S. Raghava; Asok De (International Journal of Antennas and Propagation)
A novel metamaterial-inspired patch antenna is proposed, wherein a 2-segment SRR Labyrinth metamaterial is embedded inside the antenna substrate. It is observed that upon incorporation, the bandwidth widens to around 600% and VSWR improves by approx. 1.5% and the antenna is miniaturized by 400%. The Nicolson-Ross-Weir (NRW) method has been used to retrieve the material parameters from transmission and reflection coefficients.